Severe and critical COVID-19 in pregnancy: A case series from Montreal. (September 2021) - Trahan, Marie-Julie; Malhamé, Isabelle; Mitric, Cristina; Simard, Camille; Lipes, Jed; Abenhaim, Haim A
Background: Optimal obstetric management for women with coronavirus disease (COVID-19) is not known. We describe the management of six pregnant women requiring in-hospital care for severe COVID-19. Methods: A retrospective chart review was conducted to identify pregnant women who tested positive for Severe Acute Respiratory Syndrome Coronavirus (SARS-CoV-2) between 15 March and 30 June 2020. A subset of women meeting criteria for severe COVID-19 was included. Results: Four women required non-invasive supplemental oxygen therapy and two required mechanical ventilation. Four women were discharged from hospital undelivered and two required preterm delivery. One woman had a pulmonary embolism, and two required re-admission for worsening symptoms. Conclusion: Management of pregnant women with severe COVID-19 is complex and should involve multidisciplinary expertise. Avoiding early delivery may be a safe option. We recommend an individualized approach to care, including careful consideration of the expected risks and benefits of expectant obstetric management versus delivery.